1982
DOI: 10.1002/pd.1970020108
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum alfa‐fetoprotein levels in the pregnancy complicated by hypertension

Abstract: Maternal serum alpha-fetoprotein (MSAFP) was determined in patients 33 to 40 weeks pregnant, and the Iesults were analysed with consideration of the presence and quality of hypertensive disease that complicated many of the pregnancies. Patients with incompletely controlled hypertension had significantly higher MSAFP levels than control patients with pregnancies uncomplicated by any risk factor. MSAFP elevation was greatest in pre-eclampsia (301.6 k 147.6 kU/L, n = 35) >chronic hypertension with superimposed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…These findings are in keeping with reports of a study by Walters et al [7] However, it is in contrast with finding by Clayton-Hopkins et al [20] which reported significantly higher mean serum AFP levels in pre-eclamptics than in normotensive controls. However, no eclamptic was recruited into the study by Clayton-Hopkins et al [20] Pre-eclampsia was also diagnosed in the second half of pregnancy, by an increase in systolic blood pressure of 20mmHg and diastolic blood pressure of 10mmHg over a previous reading in two successive visits to the physician accompanied by either or both edema and proteinuria, in their study. The different study definition of hypertension in pregnancy used by Clayton Hopkins et al may explain why their findings are not congruent with results of this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in keeping with reports of a study by Walters et al [7] However, it is in contrast with finding by Clayton-Hopkins et al [20] which reported significantly higher mean serum AFP levels in pre-eclamptics than in normotensive controls. However, no eclamptic was recruited into the study by Clayton-Hopkins et al [20] Pre-eclampsia was also diagnosed in the second half of pregnancy, by an increase in systolic blood pressure of 20mmHg and diastolic blood pressure of 10mmHg over a previous reading in two successive visits to the physician accompanied by either or both edema and proteinuria, in their study. The different study definition of hypertension in pregnancy used by Clayton Hopkins et al may explain why their findings are not congruent with results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…This further strengthens the possible role of AFP as potential markers of severity in PIH as suggested by other studies. [5,20] Multiple linear regression analysis showed that serum AFP increased as birth weights reduced (Table 12). Serum AFP had significant association with BMI and Apgar scores when adjusted for other variables.…”
Section: Discussionmentioning
confidence: 99%
“…All the bags tested, apart from the Air-Viva, produced satisfactory results at both tidal volumes with zero carbon dioxide during the inspiratory phase (figure). With the Air-Viva, however, the inspired carbon dioxide concentration rose immediately-that is, rebreathing occurred-and after [20][21][22][23][24][25][26][27][28][29][30] seconds reached a plateau of 2%, which was then maintained throughout the five and 15 minute periods. Increasing the tidal volume did not influence this rise in inspired carbon dioxide.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…It is of interest in this discussion that excessive placental secretions of neurokinin have recently been associated with pre-eclampsia in the third trimester of pregnancy (333). It has long been known that pre-eclampsia is associated with elevated AFP levels (334,335).…”
Section: Afp Fragmentsmentioning
confidence: 99%